Diagnostics of the depth of digitalization of HR management - Gaponenko Tatiana; Malkhasyan Anastasia; Filin Nikolay; Bulatova Raykhana (E3S Web of Conferences, 2021)
The purpose of the article is to develop a methodology which assesses the level of digitalization of HR management, to identify the reasons for the gap between the actual achieved level and the desired one, and to justify management decisions related to the introduction of digital technologies. The methodology involves diagnostics of the level of digitization of HR-management in three aspects: digital competence of personnel, digital workplace, digital management system. A combined method has been proposed for the diagnosis of staff digital competences: self-diagnostic and manager's assessment on a single scale, followed by a comparison of the results. A coefficient method is proposed for estimating a digital workplace and a digital control system. The resulting conclusion on the level of digitization of an organization’s HR management is based on the benchmarking method. The implementation of measures to increase the level of digitalization of HR management, adopted on the basis of the conducted diagnostics, will allow the organization to maintain and to increase its competitive advantages by developing the necessary professional qualities of employees, the best organization of personnel management in the conditions of digitalization.